Pengaruh Hedonic Shopping Motivation Terhadap Keputusan Pembelian Konsumen pada Toko Zam Zam Premium - Sri Astuti; Irma Mardian; Juwani Juwani (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the effect of hedonic shopping motivation on consumer purchasing decisions at Zam-Zam Premium Store in Bima City. The rapid growth of the fashion industry has transformed consumer behavior, where shopping is no longer merely intended to fulfill functional needs but also serves as a source of pleasure, entertainment, and emotional satisfaction. This research employed a quantitative approach using a causal associative research design. The population consisted of all consumers who had made purchases at Zam-Zam Premium Store, while the sample comprised 96 respondents selected through purposive sampling. Data were collected using questionnaires, observations, and literature studies. The data were analyzed using validity and reliability tests, simple linear regression analysis, the t-test, and the coefficient of determination (R²) with the assistance of SPSS software. The results indicate that all research instruments were valid and reliable. The simple linear regression analysis produced the equation Y = 12.237 + 0.575X, indicating that hedonic shopping motivation has a positive effect on purchasing decisions. The t-test showed a calculated t-value of 9.305 with a significance value of 0.000 (< 0.05), confirming that the research hypothesis was accepted. Furthermore, the coefficient of determination (R²) was 0.482, indicating that hedonic shopping motivation explained 48.2% of the variation in consumer purchasing decisions, while the remaining 51.8% was influenced by other factors not examined in this study. Therefore, it can be concluded that hedonic shopping motivation has a positive and significant effect on consumer purchasing decisions at Zam-Zam Premium Store.